Phytochemical and antioxidant capacity profiles of syzygiumcumini (L.) skeelsleaves grown in Telur Bagan Kedah, Malaysia using sequential cold percolation extraction - Sukmasari, Susi; Mohd, Farah Natashah; Abdul Qader, Omar Abdul Jabbar; Doolaanea, Abd Almonem; Abdul Rahman, Mohammad Nasrin (Journal of International Pharmaceutical Research, 2018)
This study aimed to investigate the phytochemicals and antioxidant properties of Syzygiumcumini(L.) Skeels grown in Telur BaganKedah, Malaysia Syzygiumcuminiwas extracted successively in 5 different solvents which are petroleum ether, toluene, ethyl acetate, acetone, and water, using sequential cold percolation method. The dried crude extractswerecharacterized for percentage yield, total phenolic content, total flavonoid content, percentage of DPPH radical scavenging activity, and reducing power to reduce Fe3+ to Fe2+ using FRAP assay.Extracts from different solvents produced different results. Toluene extract had the highest percentage yield, and highest total phenolic content, whereas acetone extract had the highest total flavonoid content. Water extract had the highest antioxidant capacity using DPPH test, with value of 11.89 ± 1.14 mg AEAC/g of dried leaves and reducing power from FRAP assay with value of 4512.83 ± 287.73 µg AAE/g of dried leaves. Petroleum ether had the highest antioxidant capacity in terms of inhibitory concentration of DPPH, due to its lowest IC50 value.All the phytochemical and antioxidant properties of Syzygiumcumini were successfully documented, analyzed .